Assessing teacher training college tutor’s awareness of learning difficulties at a selected College in Rwanda - Edmore Chingwe; Sibonokuhle Ndlovu; Webster Mudzingwa; Jean Nizeyimana (International Journal of Studies in Inclusive Education)
This study assesses Teacher Training College Tutors’ (TTCTs) awareness of three learning difficulties (dyslexia, dyscalculia, and dysgraphia). The study sample consisted of twenty tutors at one Teacher Training College (TTC) in Rwanda. Awareness of learning difficulties was assessed through a mixed-method approach. Data was analysed using thematic and descriptive statistical techniques. Tutors were found to have an overall average awareness score of 85%. The awareness of dyslexia, dyscalculia, and dysgraphia stood at 76%, 84%, and 90%, respectively. Tutors’ awareness of strategies for mediating learning difficulties stood at 91%. TTC faced numerous challenges in the teaching and learning of students with learning difficulties. These included inadequate teaching and learning resources, training, and a packed timetable. Although tutor awareness of learning difficulties is high, tutors appear not to know much about some elements. Therefore, TTC should conduct more staff development sessions on learning difficulties in collaboration with relevant stakeholders.